Creation of Traditional Engklek Games for Children Aged 7-10 in Suka Mulia Village in 2024 - Winata, Devi Catur; Lestari, Dewi Ayu; Syaleh, Muhammad; Sumando Damanik, Alvisa Vintor; Br. Tarigan, Gita Nurgaya (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2024)
Objective. The objective of this study is to assess the viability of creating traditional games for children aged 7-10 years in Suka Mulia Village in 2024. Materials and methods. This study is a development project utilizing a Borg and Gall design. The study was carried out in Suka Mulia Village, Secanggang District, Langkat Regency. The study was carried out from March 2024 until its conclusion. A sample comprising 10 children was utilized in this study. Students were organized into groups of 10 for small group trials and 20 for large group trials. The method of data collection involved administering a questionnaire to experts in traditional games, material specialists, and child participants in Suka Mulia Village, Secanggang District, Langkat Regency. Results. The findings and conclusions drawn from this study are derived from a small group trial involving 10 children in Suka Mulia Village. The results indicated a score of 398, corresponding to a percentage of 79.6% (Quite Valid). The findings stem from a substantial group trial carried out on children aged 7-10 years in Suka Mulia Village, involving a total of 20 students. The score achieved was 917, corresponding to a percentage of 91.7% (Valid). Conclusion. That the traditional game of engklek can support the physical, social, and cognitive development of children aged 7-10 years in Suka Mulia Village. This program is effective and fun as an educational tool for children.